Multilevel regulatory governance: Establishing bank-regulator relationships at the European Banking Authority. (March 2020) - Coen, David; Salter, John-Paul
Abstract: Following the 2007–9 financial crisis, the EU strengthened its institutional apparatus for bank regulation, creating a trio of sectoral bodies, including the European Banking Authority (EBA). Various aspects of this new system have been studied, but to date, little is known about how banks engage with their new supranational regulator. We argue that such engagement fosters an interdependence between banks and regulators, thus contributing to the efficiency and robustness of the overall regulatory regime; but also that it is contingent on the regulator exhibiting the qualities of credibility, legitimacy, and transparency. These qualities are grounded in the domestic regulatory governance literature, but we suggest that they are rendered problematic by the complexities of the EU's multilevel system and, in particular, the overlap in competences between the EBA and the European Central Bank. We examine the EBA in the light of these criteria and find that banks' engagement remains pitched towards established national regulators and the EU's legislative arena. This poses concerns for the efficacy of agency governance in the EU's regulatory regime for banking.